Impact of Kolb’s experiential learning theory-based nursing on caregiver burden and psychological state of caregivers of dementia patients - Xu Yue; Lu Jingzheng; Yu Xinting; Ding Heguo (Open Medicine, 2025)
Family caregiving for dementia patients is a challenging task, with profound effects on caregivers’ physical and mental well-being. The purpose of this study was to explore the impact of Kolb’s experiential learning theory on the caregiving burden and psychological status of caregivers for dementia patients.